Comparison of DASS-21, PHQ-8, and GAD-7 in a virtual behavioral health care setting - Peters, Lila (Heliyon, 2021)
BACKGROUND: Validated depression and anxiety symptom screeners are commonly used in clinical settings. How results from different brief depression and anxiety symptom assessment tools compare to each other is not well established, especially in real world healthcare settings. This study aimed to compare the Depression Anxiety Stress Scales 21 Depression scale (DASS-Depression) and Anxiety (DASS-Anxiety) scale to the Patient Health Questionnaire 8 (PHQ-8) and Generalized Anxiety Disorder 7 (GAD-7) respectively, in a real-world virtual behavioral healthcare setting. METHODS: This was a retrospective comparison study of clinical data from a population of adults who completed a consultation via telephone or secure video with a licensed therapist as part of a standardized, evidence-based, virtual behavioral therapy program for individuals with comorbid medical and behavioral health conditions. The joint distributions and correlations between scores yielded by each depression and anxiety scale were assessed using descriptive and Spearman correlation statistics. RESULTS: The DASS-Depression and PHQ-8 were highly correlated (r = .71; p=<.001); the DASS-Anxiety and GAD-7 correlation was also high (r = .61; p=<.001). The PHQ-8 categorized more individuals as having above-threshold depression scores versus the DASS-Depression (71.5% vs. 43.5%; p < .001). The GAD-7 categorized more individuals as having above-threshold anxiety scores versus the DASS-Anxiety (59.0% vs. 45.0%; p < .001). LIMITATIONS: This study compared results yielded by validated screeners, precluding conclusions related to the validity of screener results. CONCLUSIONS: The DASS-Depression and PHQ-8 and the DASS-Anxiety and GAD-7 similarly ranked symptom severity. The PHQ-8 and GAD-7 were more likely than the DASS-21 Depression or Anxiety scales to classify individuals as having above-threshold symptom severity.